2018
DOI: 10.1371/journal.pone.0205774
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about people with albinism in Uganda: A qualitative study using the Common-Sense Model

Abstract: Albinism includes a group of inherited conditions that result in reduced melanin production. It has been documented across the world, with a high frequency in sub-Saharan Africa. There is very little published research about the lives of people with albinism, but available evidence shows that myths abound regarding their condition. They are feared, viewed with suspicion and believed to have supernatural powers. In this study we explored the links between beliefs, myths, traditions and positive/negative attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
2
36
0
2
Order By: Relevance
“…16 Previous studies have revealed that discrimination and stigma are major challenges in the day-to-day life of PWA in various regions of Africa. [9][10][11] Societal discrimination of PWA is also highly prevalent in the DRC and was reported by 67.4% of patients. Surprisingly, 24.4% of patients experienced discrimination from their own close family and friends, even when they were not the only PWA in their family.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…16 Previous studies have revealed that discrimination and stigma are major challenges in the day-to-day life of PWA in various regions of Africa. [9][10][11] Societal discrimination of PWA is also highly prevalent in the DRC and was reported by 67.4% of patients. Surprisingly, 24.4% of patients experienced discrimination from their own close family and friends, even when they were not the only PWA in their family.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Discrimination can have far-reaching effects, limiting the ability of PWA to properly engage in education, social relationships, and healthcare. [9][10][11] In comparison, PWA in South Africa have reported better health and increased self-esteem when governmental and nongovernmental institutions were able to provide reliable educational, social, and medical resources. 9,17,18 Campaigns are needed to increase albinism awareness Limitations of this study include the small sample size, limited follow-up period, and incomplete data including lack of histological diagnosis for many cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, recent research in Cameroon demonstrated that PWA experienced violation of their human rights, stigma, and discrimination, primarily due to their skin colour (Dapi, Tambe, & Monebenimp, ). Bradbury‐Jones, Ogik, Betts, Taylor, and Lund () investigated beliefs, myths, traditions, and attitudes that surround people with albinism in Uganda. They found that most Ugandans feared PWA, viewed them with suspicion, and believed them to possess supernatural powers.…”
Section: Introductionmentioning
confidence: 99%